ANALISIS KLASTER UNTUK SEGMENTASI PEMIRSA PROGRAM BERITA SORE STASIUN TV SWASTA - Rosiatun, Aan; Widiharih, Tatik; Safitri, Diah (MEDIA STATISTIKA, 2010)
A procedure market segmentation is designing the market segmentation use the method of cluster k-means analyze which applied in process designing the market evening news audiences on tv chanels. The process of grouping audiences into each segment which formed, based on likeness of characteristic owned and it formed 3 market segment evening news audiences, that is audiences group who give low evaluation, audiences group who give enough evaluation, and audiences group who give high evaluation. Result from the market segmentation with case study at Pangkah district Tegal regency got first cluster is 25.2 %, second cluster is 46 %, and third cluster is 28.8 %. Marketing strategy can target be old > 20 years because it has members total of cluster is biggest. The result can be used by a television company to determine marketing strategy. Keywords: Characteristic, Market Segmentation, Cluster K-Means Analysis